Squirrel cage induction motor predictive direct torque control based on multi-step delay compensation - Najimaldi M. Abbas (Institute of Advanced Engineering and Science, 2021)
The squirrel cage induction motor direct torque control main problems due to torque and large stator flux pulsation. In this an improved model predictive direct torque control algorithm considering multi-step delay compensation is proposed. At each sampling moment, predict the stator flux linkage and torque at the next moment under each voltage vector. The optimal voltage vector deviation from the stator flux linkage reference value and torque reference value are selected as the minimum objective function. Aiming at the problem of one-shot delay in digital control systems, a multi-step predictive delay compensation measure is studied. Simulation shows that the algorithm can effectively reduce torque and stator flux pulsation, reduce current harmonic distortion, and solve the delay problem in digital systems.